2009
DOI: 10.1016/j.nutres.2009.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Combined selenium and vitamin C deficiency causes cell death in guinea pig skeletal muscle

Abstract: Combined antioxidant deficiencies of selenium and vitamin E or vitamin E and vitamin C in guinea pigs result in clinical illness. We hypothesized that combined selenium and vitamin C deficiency would have clinical consequences because in vitro interactions of these antioxidant nutrients have been reported. Since guinea pigs are dependent on dietary vitamin C, weanling male guinea pigs were fed selenium-deficient or control diet for 15 weeks prior to imposing vitamin C deficiency. Four dietary groups were forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…These results contrast with our previous findings where fish had combined VitE and vitamin C deficiencies that caused significant myopathy in the E− adults and impaired startle responses [22]. These latter findings were expected because compound antioxidant-nutrient deficiencies frequently lead to significantly more severe pathophysiological (myopathic) consequences than do isolated deficiencies [36,37]. When E− fish were fed a VitE-deficient diet with excess vitamin C (3500 mg/kg) and soybean lecithin (which has only 20% PC), we found that the E− swam slower and with multiple taps became speedier [21].…”
Section: Discussioncontrasting
confidence: 93%
“…These results contrast with our previous findings where fish had combined VitE and vitamin C deficiencies that caused significant myopathy in the E− adults and impaired startle responses [22]. These latter findings were expected because compound antioxidant-nutrient deficiencies frequently lead to significantly more severe pathophysiological (myopathic) consequences than do isolated deficiencies [36,37]. When E− fish were fed a VitE-deficient diet with excess vitamin C (3500 mg/kg) and soybean lecithin (which has only 20% PC), we found that the E− swam slower and with multiple taps became speedier [21].…”
Section: Discussioncontrasting
confidence: 93%
“…In humans, the rate of disappearance of vitamin E in response to oxidative stress is dependent on vitamin C status (Bruno et al, 2005). In guinea pigs, vitamin C deficiency alone does not cause significant muscle damage, but does exacerbate vitamin E or selenium deficiencies and the resultant myopathies (Hill et al, 2003; Hill et al, 2009). Like humans and guinea pigs, zebrafish require both vitamins in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that muscle health is dependent on an adequate supply of dietary vitamin E which includes T3 [180]. A diet deficient in vitamin E causes profuse myocyte necrosis and ultimately leads to lethal muscular dystrophy, as demonstrated in various animal model studies [181][182][183][184].…”
Section: Effects Of Tocotrienol On Muscle Diseasesmentioning
confidence: 99%